Isolation and Characterization of a Porcine Transmissible Gastroenteritis Coronavirus in Northeast China - Yuan, Dongwei; Yan, Zihan; Li, Mingyue; Wang, Yi; Su, Mingjun; Sun, Dongbo (Frontiers in Veterinary Science, 2021)
Transmissible gastroenteritis virus (TGEV) is a coronavirus (CoV) that is a major pathogenity of viral enteritis and diarrhea in suckling piglets, causing high morbidity and mortality. In this study, a TGEV strain HQ2016 was isolated from northeast China and characterized its genome sequence and pathogenicity. The phylogenetic analysis indicated that the TGEV HQ2016 strain was more similar to the TGEV Purdue cluster than to the Miller cluster. Both recombination and phylogenetic analysis based on each structural and non-structural gene revealed no recombination event in the HQ2016 strain. Experimental infection study using colostrum-deprived newborn piglets successfully showed that the HQ2016 can cause clinical symptoms including anorexia and yellow-to whitish watery diarrhea, which are characteristics of TGE, in the inoculated piglets 48 hours post inoculation. These results provide valuable information about the evolution of the porcine CoVs.